Pressure-induced redistribution in density of states and reemergence of superconductivity in AgSnSe2 - Cuiying Pei; Juefei Wu; Weizheng Cao; Yuyang Jiang; Qi Wang; Yi Zhao; Junjie Wang; Tianping Ying; Yanpeng Qi (iScience)
Summary: The intricate relationship between superconductivity and disorder is a captivating subject within condensed matter physics. Strong disorder suppresses superconductivity and induces a superconductor-insulator transition. However, below a certain critical degree of disorder, the superconductivity critical temperature (Tc) can be enhanced. Herein, we present evidence of pressure-induced reemergence of superconductivity in a strongly disordered 3D superconductor AgSnSe2. A structural phase transition from NaCl- to CsCl-type structure occurs, coinciding with the emergence of the second superconducting state. First-principles calculations suggest that the partial density of states in Se atoms exhibits a sharp elevation around the transition pressure, which is related to the secondary superconducting state. Our study illustrates AgSnSe2 as a promising platform to explore the comprehensive effects among disorder, high pressure, and superconductivity, offering insights for subsequent experimental and theoretical studies.